2004
DOI: 10.1002/ejsp.189
|View full text |Cite
|
Sign up to set email alerts
|

Perceived in‐group threat as a factor moderating the influence of in‐group norms on discrimination against foreigners

Abstract: Within the framework of an intergroup relations paradigm, three studies analysed the role of in-group threat in intergroup discrimination and the influence of in-group norms on intergroup discrimination. The first study showed that perceived socio-economic threat underlies Swiss nationals' prejudice and discrimination toward foreigners in Switzerland. The second and third studies experimentally tested the hypotheses, first, that variations in perception of in-group threat will produce change in initial discrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 54 publications
1
44
0
7
Order By: Relevance
“…In an attempt to understand why immigrants remained a target of prejudice in Switzerland despite prevailing anti-discrimination norms, Falomir-Pichastor, Munoz-Rojas, Invernizzi, & Mugny (2004) showed that economic threat moderated the impact of antidiscrimination norms on discrimination. Experimentally induced anti-discrimination norms reduced discrimination of immigrants only when threat was low (i.e., when fictitious research findings demonstrated that a high proportion of immigrants did not increase unemployment).…”
Section: Migration and Multiculturalism 24mentioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to understand why immigrants remained a target of prejudice in Switzerland despite prevailing anti-discrimination norms, Falomir-Pichastor, Munoz-Rojas, Invernizzi, & Mugny (2004) showed that economic threat moderated the impact of antidiscrimination norms on discrimination. Experimentally induced anti-discrimination norms reduced discrimination of immigrants only when threat was low (i.e., when fictitious research findings demonstrated that a high proportion of immigrants did not increase unemployment).…”
Section: Migration and Multiculturalism 24mentioning
confidence: 99%
“…Experimental research, in turn, addresses these critiques by manipulating threat perceptions in various ways (see also Schlueter, Schmidt, & Wagner, 2008, for longitudinal evidence). Many studies use fictitious newspaper articles, editorials, research findings or policy framings to manipulate threat perceptions, thereby simulating dissemination of threat-based arguments in the media and the public sphere (e.g., Esses et al, 1998;Falomir-Pichastor et al, 2004;Pratto & Lemieux, 2001). However, controlled experiments remain artificial situations-frequently using student populations-and thus cannot conclusively show the conditions under which threat shapes immigration policy stances among the general population in the real world.…”
Section: Migration and Multiculturalism 32mentioning
confidence: 99%
“…Research has shown that norms guide people's cognition and behaviour (for a review, see Cialdini, Kallgren, & Reno, 1991) and help individuals to orient themselves towards others in INTERMINORITY EXTENDED CONTACT 7 intergroup situations (e.g., Falomir-Pichastor, Muñoz-Rojas, Invernizzi, & Mugny, 2004;Jetten, Spears, & Manstead, 1996).…”
Section: Ingroup Normsmentioning
confidence: 99%
“…Conformity to group norms proves to depend on perceived in-group threat and on the extent to which the norm provides an appropriate answer to such a threat. Falomir-Pichastor et al (2004) observed that Swiss nationals conformed to an antidiscrimination in-group norm (i.e., they reduced discrimination against foreigners) when the out-group was perceived as nonthreatening (i.e., when foreigners were not perceived as taking jobs nor increasing nationals' unemployment). However, the same norm did not obtain any influence, and a counterconformity effect even tended to appear, when the out-group was perceived as threatening.…”
Section: Reducing Xenophobiamentioning
confidence: 99%